SUBSTITUTION OF FISH MEAL WITH EARTHWORM MEAL (Lumbricus rubellus) ON FEED TOWARD UNSATURATED FATTY ACIDS, TRIGLYCERIDE, LOW DENSITY LIPOPROTEIN (LDL) AND HIGH DENSITY LIPOPROTEIN (HDL) CONTENT ON NILE TILAPIA’S (Oreochromis niloticus) MEAT - Guruh Firnanda Reynaldy (Department of Aquaculture, 2019)
Earthworm meal can be used to replaced fish meal because earthworm meal has higher protein than fish meal. Earthworms can be used as meal which can replace fish meal which has a lower protein value than earthworm meal. The purpose of this study was to determine the effect of substitution of fish meal with earthworm meal can increase the content of unsaturated fatty acids and HDL and reduce triglycerides and LDL on tilapia’s meat. This study was designed using a completely randomized design with 4 treatments and 5 replications. The dose given at each treatment is 0%, 30% 35%, 40%, 45%. Treatments were conducted for 45 days, by feeding 5% of the weight of biomass with a frequency of 3 times a day. The results of this study were able to increase the content of oleic acid, triglycerides and HDL and reduce LDL (P <0.05). Substitution of earthworm meal has no effect on the content of omega 3 and omega 6 meat of tilapia (P> 0.05).